Facebook and Public Relations in Higher Education - Ludvik Eger; Dana Egerova; Miroslav Kryston (Romanian Journal of Communications and Public Relations, 2019)
Nowadays It is essential for universities and faculties to interact on-line with their potential applicants, current students as well as other stakeholders. In recent years, social media such as Facebook has provided higher education institutions with new means of communication with their target groups. The purpose of this study is to explore the use of the most popular social network Facebook by selected faculties in the Czech Republic and Slovakia and to provide a set of practical benchmarks on successful communication with public. To answer presented research questions, a convergent parallel mixed-methods research design was used. Firstly, a focus group investigation was put forward to clarify what communication channels are generally used by applicants and students when searching and sharing information about faculties. Secondly, a quantitative data analysis, based on data mining using tools such as Power BI and Netvizz, was presented. Data for year 2017 obtained from sixteen Facebook profiles of selected faculties were used. The findings provide evidence on the use of Facebook by an institution – customer communication by the faculties. Furthermore, they reveal that different message features generated different customer behaviour. The study contributes to a better understanding of marketing-related activities on social media in higher education.